PENINGKATAN PRODUKTIFITAS UNIT CRUSHING PLANT III UNTUK MENCAPAI TARGET PRODUKSI DI PT. BATU KALI WELANG AMPUH KABUPATEN PASURUAN PROVINSI JAWA TIMUR - Flaminggo Gingga; Abdul Rauf; Rhizky Maulana (Retii, 2018)
Batu Kali Welang Ampuh (BKWA) Ltd is a company engaged in andesite stone mining business. The production target is planned to achieve 1000 tons/days. In fact, based on the observation of the dump truck loading and unloading as well as on the calculation of the existing equipment capability in crushing plant III unit, this company only reached the production target 364 tons/day or 121.3 ton/hour. So, in order to achieve the desired production target, a research on the crushing unit needs tobe done. Based on the observations and calculations from the field data, the condition of the usage avaibility value of mechanical devices obtained : hopper was 97.60%, vibrating feeder was 100%, jaw crusher was 92.27%, belt conveyor was 83.48%, and vibrating screen was 82.63%. In order to increase the production, there should be improvement efforts on working time. So, by the improvement of the time constrain, the effective working time improved from 177 minutes/day to 385 minutes/day or 6.42 hours/day. Thus, it will increase the production target from 364 tons/day to 1001.52 tons/day.